Full‐scale experiments to study shock waves generated by the rupture of a high‐pressure pipeline. Issue 4 (24th October 2016) - Wu, JianYuan; Long, Yuan; Ji, Chong; Xu, QuanJun; Mao, YiMing; Song, KeJian
Abstract : Large‐scale experimental investigations were conducted on the flow structures and intensity of shock waves generated by the rupture of a high‐pressure pipeline. In the experiments, the bursting of pipes was caused by an initial crack introduced on the upper center of the pipe. The crack velocity, pressure‐time trace and explosion overpressure were measured. The intensity of the far‐field explosion overpressure was estimated based on the extent of damage to buildings. The results demonstrated that the shock waves generated by a pipeline rupture indicate an extremely strong directional effect in the near‐field, and their measured speeds were similar to the speeds calculated from theory. Not all of the gas energy participates in the explosion of a long pipeline, and an equation is established to calculate the gas energy involved in a pipeline blast. The TNT equivalency approach was used to calculate the explosion overpressure, and the impulse generated by the pipeline rupture and its applicability were discussed. © 2016 American Institute of Chemical Engineers Process Saf Prog 35: 414–423, 2016